A simple method for the assessment of arterial stiffness in pre-eclamptic patients. (December 2014) - Oylumlu, Mustafa; Oylumlu, Muhammed; Yuksel, Murat; Yildiz, Abdulkadir; Bilik, Mehmet Zihni; Akil, Mehmet Ata; Ozler, Ali; Acet, Halit; Ertas, Faruk; Alan, Sait
Abstract Background: Arterial stiffness (AS), the term describes the rigidity of arterial walls, and its hemodynamic results have been shown to be associated with increase in future cardiovascular events. Women with pre-eclampsia in their past pregnancies have a higher risk of developing cardiovascular disease later in life. The goal of this study was to assess AS using a non-invasive and simple oscillometric method in pregnant women with and without pre-eclampsia. Methods: Ninety pregnant women, forty-five of which had pre-eclampsia, were included in the study. The vascular measurements were performed with a Mobil-O-Graph 24 h PWA Monitor, an automatic oscillometric device. Statistical analysis was performed using the Chi-square, independent sample t-test or the Mann–Whitney U test, Pearson correlation, and linear regression tests. Results: All the vascular function parameters were significantly higher in the patients with pre-eclampsia. The pulse wave velocity (PWV) values found in the pre-eclampsia group were positively correlated with gestational age, maternal age, glucose level, creatinine level, augmentation index, and central blood pressure. Using linear regression analysis, the PWV values were confirmed to be positively correlated with gestational age, maternal age, and central systolic blood pressure. The women with severe pre-eclampsia had significantly higher blood pressures, PWV values, augmentation indices, and cardiac outputs when compared with the patients with mild pre-eclampsia. Conclusion: Oscillometric PWV measurement is already accepted as the most reproducible quick, simple, and inexpensive non-invasive method for the assessment of large artery stiffness. It can be applied to evaluate the AS and also aid in detecting future cardiovascular risk of patients with pre-eclampsia.